2013
DOI: 10.1007/8904_2013_233
|View full text |Cite
|
Sign up to set email alerts
|

Socio-emotional Problems in Children with CDG

Abstract: Background: Congenital disorders of glycosylation (CDG) form a group of inherited metabolic diseases. Although the clinical presentation shows extreme variability, the nervous system is frequently affected. Several parents of our patients diagnosed with CDG reported behavioral problems, including mood swings, depressive behavior, and anxiety. This raised the question whether patients with CDG have an increased risk for socio-emotional problems.Methods: We evaluated 18 children with confirmed CDG. The Child Beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Whilst 37.9% of non-PMM2-CDG patients were diagnosed after six, only 17.2% of PMM2-CDG were diagnosed at the same age range [25]. Witters et al [29] and van de Loo et al [93] reported the same age range for the diagnosis of PMM2-CDG and other CDG, respectively: between 2 weeks and 21 years.…”
Section: Summary Of Demographic and Clinical Characteristicsmentioning
confidence: 98%
See 1 more Smart Citation
“…Whilst 37.9% of non-PMM2-CDG patients were diagnosed after six, only 17.2% of PMM2-CDG were diagnosed at the same age range [25]. Witters et al [29] and van de Loo et al [93] reported the same age range for the diagnosis of PMM2-CDG and other CDG, respectively: between 2 weeks and 21 years.…”
Section: Summary Of Demographic and Clinical Characteristicsmentioning
confidence: 98%
“…Four studies reported the mean or range of age at diagnosis [25,29,47,93], showing a propensity for young patients. For instance, Francisco et al [25] reported that 74% CDG patients were diagnosed before 5 years of age, and in 2000, 54% of diagnosed patients were below 10 years of age [168].…”
Section: Summary Of Demographic and Clinical Characteristicsmentioning
confidence: 99%
“…Endocrine disturbance and thrombotic complications are common at any age (Linssen et al 2013). Patients might have severe communication problems but a cheerful habitus (van de Loo et al 2013). Many patients survive to adulthood, losing the syndromal aspects of PMM2-CDG.…”
Section: Clinical Phenotype and Recognizable Phenotypes In Cdgs Involmentioning
confidence: 99%
“…In more than two thirds of the children with CDG it was observed a variation in the abnormal behavior identification test -The Child Behavior Checklist (CBCL). The authors emphasize the importance of psychological screening tests among patients with disorders of glycosylation, as a group of an increased risk of developing socioemotional disorders, including depressive behavior [12].…”
Section: Genetic Causesmentioning
confidence: 99%